Plant-available water, stem diameter variations, chlorophyll fluorescence, and ion content in Pistacia lentiscus under salinity stress - Castillo-Campohermoso, Marco Antonio; Broetto, Fernando [UNESP]; Rodríguez-Hernández, Ana Margarita; de Abril Alexandra Soriano-Melgar, Lluvia; Mounzer, Oussama; Sánchez-Blanco, María Jesús (My University, 2020)
The aim of this study was to investigate the physiological and hydric adaptability of Pistacia lentiscus (lentisco) to saline irrigation conditions. Plants of lentisco were subjected to four salinity treatments in the irrigation water (0, 50, 100 y 150 mM NaCl) during three months in a growth chamber in order to identify possible tolerance mechanisms to salinity stress. The results showed a reduction of aerial growth parameters, mainly in the 150 mM of NaCl treatment. The root biomass did not change; however, the root hydraulic conductivity was modif ied. This behavior was related with decreases in leaf water potential values both at morning and midday. With the increase of salinity in the irrigation water, the radial growth of stem of the plants was proportionally decreased, and Cl- and Na+ content at minimum and maximum illumination in leaves and roots increased. Stomatal conductance decreased in the plants with higher salinity level, although chlorophyll content and fluorescence were not affected by the salinity treatments. Although the growth rates were statistically affected in all the treatments, the plants were able to resist the salt stress through changes in the leaf structures, related to a reduction of water losses via transpiration.
Disponibilidad de agua, variaciones en el diámetro del tallo, fluorescencia de la clorofila y contenido iónico en Pistacia lentiscus bajo estrés salino
Keywords: Hydraulic conductivity; Mediterranean shrub; Nutrient content; Water relations